THE STRATEGIC ROLE OF NITRATES TO SOIL PERFORMANCE AND CARBON SEQUESTRATION - Popescu, Lavinia; Adela , Sorinela Safta; Nancu, Dumitru (Economics of Agriculture, 2022)
The aim of this research is to highlight an image of the risks of nitrates and soils but also of the global capacities to adapt to a sustainable agricultural economy. The article also focused on the ability to implement methods of proper use of nitrates to improve soil capacities as a means of sequestration of C. Productivity of crops with a high capacity to fx nitrogen in the soil contributes to the fulfillment of the mitigation mechanism and reduction of greenhouse gas emission. The main result of the research is the identification of adequate nitrate management in improving soil quality, as well as the use of crop rotation as a means of sequestering C at soil level. Methodologically, the conditions for optimizing the capture of C from the soil by adequate management of nitrates were followed. Research will help to understand the problems of land use in the context of climate change, as well as provide information on GHG emissions by advancing strategies that contribute to the effort to decarbonise agriculture through the proper treatment of agricultural land.